El veneno y el mosquito: aspectos epistemológicos de la etiología y la profilaxis de la fiebre amarilla Poison and the mosquito: epistemological aspects of the etiology and prophylactics of yellow fever - Sandra Caponi (História, Ciências, Saúde: Manguinhos, 2000)
En el II Congreso Médico Latinoamericano (Buenos Aires, 1904) se discutieron las estrategias que Argentina y Brasil delinearon para combatir la fiebre amarilla. El análisis de la controversia entre sanitaristas brasileños y argentinos en torno a los modelos explicativos y a las estrategias de profilaxis internacional de esa enfermedad, nos permite una comprensión epistemológica de la ruptura operada por la emergencia de la medicina de los vectores. Este capítulo de la historia de la medicina latinoamericana constituye una oportunidad privilegiada para analizar esa reorganización del saber que permitió integrar seres intermediarios vivos en el discurso médico y epidemiológico. The strategies against yellow fever developed by Argentina and Brazil were discussed at the Second Medical Congress of Latin America which was held in Buenos Aires in 1904. The study of the controversy between physicians from Argentina and Brazil around the existing explanatory models of this illness and the international prophylactic strategies in use at the time enables an epistemological understanding of the breakthrough brought about by the emergence of the medicine of vectors. This chapter of Latin American medicine history constitutes a unique opportunity to analyze that reorganization of knowledge, which permitted the inclusion of intermediary living beings into the medical and epidemiological discourse.